Streptococcus salivarius-derived ilexgenin A alleviates pneumonia through the gut-lung axis - Xintao Huang; Rong Wu; Xiaoqi Liang; Zhichao Yu; Ping Qin; Ze Wang; Peiheng Guo; Yunong Zeng; Zhengzheng Yan; Wei Xiao; Yun Ma (mSystems)
ABSTRACT The alteration of gut microbiota during critical illness is associated with adverse clinical outcomes. This connection between intestinal dysbiosis and poor outcomes has prompted the idea that restoring healthy microbial communities could offer a novel approach to life-support treatment for patients with severe pneumonia. In this study, using 16S rRNA sequencing and fecal microbiota transplantation (FMT), we demonstrated that alterations in intestinal microbiota structure during pneumonia exacerbate disease outcomes. A notable feature of these alterations is the reduction in the relative levels of Streptococcus salivarius (S. salivarius). In combination with metabolomics analysis, we found that the administration of S. salivarius increased the level of ilexgenin A (IA) in mice, which enhances the resistance of mice to Pseudomonas aeruginosa (P. aeruginosa)-induced pneumonia. Mechanistically, IA regulates lipopolysaccharide-induced overexpression of macrophage inflammation through Toll-like receptor 4 (TLR4)-mediated NF-κB and MAPK signaling pathways. Our findings reveal the role of the microbial–immune axis in pneumonia, highlighting the potential of S. salivarius and IA in providing promising treatment strategies for pneumonia.IMPORTANCEOne of the major challenges faced by the clinical microbiome research community is to convert the connections between dysbiosis and negative clinical outcomes into rationalized and targeted therapeutic interventions. In the present work, 30 fecal samples from pneumonia and non-pneumonia patients were subjected to FMT and 16S rRNA analysis. The results revealed that a characteristic feature of gut microbiota dysbiosis in pneumonia hosts is the reduction of S. salivarius. Supplementation with S. salivarius can effectively enhance the resistance of mice to P. aeruginosa pneumonia. Moreover, we confirmed the anti-inflammatory effects of IA derived from S. salivarius both in vivo and in vitro. Thus, these findings enhance our understanding of how gut microbiota influences the outcomes of pneumonia and underscore the potential of S. salivarius as a precision microbial therapeutic for combating pneumonia.